Estimation of the Influence of Surface Soil Layers on the Parameters of Maximum Reaction Spectra - Evgeny N. Kurbatskiy; Ekaterina A. Pestriakova; Shahd A. Hussein (Structural Mechanics of Engineering Constructions and Buildings)
Surface layers are usually composed of relatively loose soils that differ significantly in seismic characteristics from deeper layers. This makes it difficult to apply general initial seismic information that does not take into account local geotechnical conditions. In general, seismic effects are given in the form of maximum response spectra for rocky or rigid soils. To take into account local geological conditions, soil correction factors are used, which do not always correctly describe the amplification of vibrations. For obtaining analytical relationships, the problem-solving technique of the theory of elasticity based on the properties of the Fourier image of finite functions was used. Using the reciprocity theorem, the displacements of the free surface from the load at the interface, which is given by the incident wave, have been determined. The methods of setting initial seismic effects in modern norms documents of different countries are described. A methodology is developed that allows to take into account the influence of soft soil layers on the parameters of the maximum response spectra. The expression for the amplification coefficients of the maximum response spectra in the surface layers of soils is obtained, which allows to estimate the local geotechnical conditions more accurately, taking into account the resonance effects of surface vibrations. An example of determining the amplification coefficients of ground vibrations for the ground conditions of the Syrian Arab Republic is given.